Asymmetric Hydrogenation of 3‐Substituted Pyridinium Salts. Issue 28 (3rd June 2016) - Renom‐Carrasco, Marc; Gajewski, Piotr; Pignataro, Luca; de Vries, Johannes G.; Piarulli, Umberto; Gennari, Cesare; Lefort, Laurent
Abstract: The use of an equivalent amount of an organic base leads to high enantiomeric excess in the asymmetric hydrogenation of N‐benzylated 3‐substituted pyridinium salts into the corresponding piperidines. Indeed, in the presence of Et3 N, a Rh‐JosiPhos catalyst reduced a range of pyridinium salts with ee values up to 90 %. The role of the base was elucidated with a mechanistic study involving the isolation of the various reaction intermediates and isotopic labeling experiments. Additionally, this study provided some evidence for an enantiodetermining step involving a dihydropyridine intermediate. Abstract : Ariadne′s thread : The asymmetric hydrogenation of 3‐substitued pyridines has been achieved with up to 90 % ee . The use of an equivalent amount of an organic base turned out to be crucial to avoid unwanted pathways leading to non‐enantioselective reduction. An in‐depth investigation of the mechanism revealed a labyrinth of hydrogenation pathways with many dead ends (see figure).